2016
DOI: 10.1590/s1984-29612016029
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Sarcocystis neurona, Toxoplasma gondii and Neospora spp. among horses in the south of the state of Minas Gerais, Brazil

Abstract: The present study used the indirect fluorescent antibody test (IFAT) to determine the seroprevalence of Sarcocystis neurona, Toxoplasma gondii and Neospora spp., and evaluated the variables associated with these infections among 506 apparently healthy horses, reared in the south of the state of Minas Gerais, Brazil. This study was conducted between April 2012 and October 2013. Among the horses, the true prevalence of S. neurona was 26% (95% CI: 22.0-30.4%), T. gondii 19.9% (95% CI: 15.5-24.8%) and Neospora spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
4
13
0
7
Order By: Relevance
“…In the present study, seropositivity to T. gondii was 47.2% (93/197), which is high when compared to similar studies (DUBEY et al, 1999a, b), but similar results were found in Egypt (GHAZY et al, 2007). In state of Minas Gerais, Brazil, Ribeiro et al (2016) showed a wide dispersion of T. gondii among horse farms, revealing that in 71.6% of the assessed farms, at least one presented one seropositive equine. The great differences in seroprevalence may be associated with various factors, including the type of feed given and the source of the water provided to animals; the intrinsic resistance to infection of horses tested; the population density of domestic or wild cats in the environment; environmental conditions; and the type of diagnostic test used (KOUAM et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the present study, seropositivity to T. gondii was 47.2% (93/197), which is high when compared to similar studies (DUBEY et al, 1999a, b), but similar results were found in Egypt (GHAZY et al, 2007). In state of Minas Gerais, Brazil, Ribeiro et al (2016) showed a wide dispersion of T. gondii among horse farms, revealing that in 71.6% of the assessed farms, at least one presented one seropositive equine. The great differences in seroprevalence may be associated with various factors, including the type of feed given and the source of the water provided to animals; the intrinsic resistance to infection of horses tested; the population density of domestic or wild cats in the environment; environmental conditions; and the type of diagnostic test used (KOUAM et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…T. gondii infections in equines have been reported in Brazil, with variable antibody detection rates (DUBEY et al, 1999a;RIBEIRO et al, 2016). In the present study, seropositivity to T. gondii was 47.2% (93/197), which is high when compared to similar studies (DUBEY et al, 1999a, b), but similar results were found in Egypt (GHAZY et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In Brazil different rates of occurrence of antibodies against T. gondii, Neospora spp., and S. neurona among horses, and antibodies against T. gondii and N. caninum in dogs have been reported (LOCATELLI-DITTRICH et al, 2006;PAULAN et al, 2013;GENNARI et al, 2016;RIBEIRO et al, 2016).…”
mentioning
confidence: 99%
“…and anti-S. neurona antibodies in horses were similar to what has been found in other studies in Brazil. Ribeiro et al (2016) found that 23.9% (107/506) and 26% (117/506) of the horses were seropositive for Neospora spp. and S. neurona, respectively in Minas Gerais, by means of IFAT.…”
mentioning
confidence: 99%